Tax Incidence and Demand Elasticity: A Theoretical and Analytical Study of Tax Burden Distribution in Modern Markets - Akmal oglu, Turayev Alijon; Yakshibayev Sevinchbek Asror oglu (Journal of Innovation in Education and Social Research, 2026)
Research objectives: This study aims to provide a comprehensive analysis of how price elasticity of demand influences the distribution of tax burden between consumers and producers within the framework of tax incidence theory. It also seeks to clarify the behavioral and economic mechanisms underlying tax shifting. Design/Methodology/Approach:The research is based on a theoretical and analytical framework utilizing standard microeconomic supply and demand models. A comparative static approach is applied to examine how different elasticity conditions affect tax burden allocation. Graphical and conceptual analysis are also used to illustrate equilibrium adjustments. Research findings: The findings indicate that the actual burden of taxation is primarily determined by demand elasticity rather than statutory tax assignment. In markets characterized by inelastic demand, consumers bear a larger share of the tax burden through increased prices. Conversely, in markets with elastic demand, producers absorb a greater portion of the tax due to reduced ability to shift costs onto consumers. Additionally, the study shows that taxation leads to varying levels of quantity reduction and welfare loss depending on elasticity conditions. Theoretical contributions/Originality: This study extends classical tax incidence theory by integrating elasticity-based behavioral responses and emphasizing the asymmetric adjustment of prices and quantities across different market structures. Implications for practitioners/policy: The results highlight the importance of considering elasticity when designing tax policies. Policymakers should target tax bases strategically to balance revenue generation, efficiency, and equity. Limitations/Research implications: The research is theoretical in nature and does not incorporate empirical data. Future studies may focus on econometric modeling and country-specific analysis.